2010
DOI: 10.1007/s10549-010-1126-2
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal exercise improves quality of life of women being treated for breast cancer, but at what cost? Randomized trial with economic evaluation

Abstract: To evaluate the efficacy and economic efficiency of a multimedia, multimodal physical activity program for women undergoing adjuvant therapy following surgery for breast cancer. We conducted a randomized trial with concurrent incremental cost-effectiveness analysis and blinded baseline, 3, 6 and 12-month follow-up assessments amongst women undergoing adjuvant therapy following surgery for breast cancer (n = 89). The intervention was a multimedia, multimodal exercise program comprising strength, balance and end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
102
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(118 citation statements)
references
References 29 publications
2
102
3
Order By: Relevance
“…2 • Three studies reported baseline utility values for patients with stage II-III disease undergoing high-dose chemotherapy (HDCT) 7 or adjuvant chemotherapy. 8,9 Baseline values were consistent across the three studies (range: 0.77−0.81) and were within the range reported for patients with early-stage disease. [7][8][9] An initial decrease in HRQoL was observed in patients undergoing HDCT, but HRQoL was restored to baseline levels at 6 months, and showed further improvements over the following 18 months.…”
Section: -6supporting
confidence: 74%
See 1 more Smart Citation
“…2 • Three studies reported baseline utility values for patients with stage II-III disease undergoing high-dose chemotherapy (HDCT) 7 or adjuvant chemotherapy. 8,9 Baseline values were consistent across the three studies (range: 0.77−0.81) and were within the range reported for patients with early-stage disease. [7][8][9] An initial decrease in HRQoL was observed in patients undergoing HDCT, but HRQoL was restored to baseline levels at 6 months, and showed further improvements over the following 18 months.…”
Section: -6supporting
confidence: 74%
“…8,9 Baseline values were consistent across the three studies (range: 0.77−0.81) and were within the range reported for patients with early-stage disease. [7][8][9] An initial decrease in HRQoL was observed in patients undergoing HDCT, but HRQoL was restored to baseline levels at 6 months, and showed further improvements over the following 18 months. 7 Similarly, HRQoL at 6 or 12 months after initiating adjuvant chemotherapy was comparable to that observed at baseline.…”
Section: -6supporting
confidence: 74%
“…Three articles were cost-effectiveness analyses (CEA), one was a combined CEA and cost-utility analysis, one was a cost-utility analysis, and one contained both a cost-minimization analysis (CMA) and a CEA. Four articles adopted a societal perspective [48,49,51,53], one used a health care system perspective [50], and one used a hospital perspective [52]. Analyses were based on multicenter RCTs [49 -51, 53], a quasiexperimental design [48], and modeling [52].…”
Section: Economic Evaluationsmentioning
confidence: 99%
“…Analyses were based on multicenter RCTs [49 -51, 53], a quasiexperimental design [48], and modeling [52]. Intervention patients were compared with a control group of patients who received no intervention [48], another intervention [49], or standard care [50 -53]. The included patients were breast cancer patients [48 -51], breast, colon, or cervical cancer patients [53], and head and neck cancer patients [52].…”
Section: Economic Evaluationsmentioning
confidence: 99%
See 1 more Smart Citation